BARRIERS TO REPORTING PATIENT SAFETY INCIDENT IN HEALTHCARE WORKERS: INTEGRATIVE LITERATURE REVIEW - Deasy Amelia Nurdin; Adik Wibowo (Indonesian Journal of Health Administration, 2021)
Background: The patient safety incident reporting systems is designed to improve the health care by learning from mistakes to minimize the recurrence mistakes, however the reporting rate is low.Aims: Integrative literature review was chosen to identify and analyze the barriers of reporting patient safety incidents by Health Care Workers (HCWs) in hospital.Methods: Searching for articles in electronic database consisting of Medline, CINAHL and Scopus resulted in 11 relevant articles originating from 9 countries.Results: There are differences but similar in barriers to reporting patient safety incident among HCWs. The barriers that occur are the existence of shaming and blaming culture, lack of time to report, lack of knowledge of the reporting system, and lack of support from the management.Conclusion: Each hospital has different barriers in reporting incident and the interventions carried out must be in accordance with the existing barriers.Keywords: barrier of reporting, incident reporting, patient safety incident